Multivariate Binomial Approximations for Asset Prices with Nonstationary Variance and Covariance Characteristics - Ho, Teng-Suan; Stapleton, Richard C.; Subrahmanyam, Marti G. (Review of Financial Studies, 1995)
In this article, we suggest an efficient method of approximating a general, multivariate log-normal distribution by a multivariate binomial process. There are two important features of such multivariate distributions. First, the state variables may have volatilities that change over time. Second, the two or more relevant state variables involved may covary with each other in a specified manner, with a time-varying covariance structure. We discuss the asymptotic properties of the resulting processes and show how the methodology can be used to value a complex, multiple exercisable option whose payoff depends on the prices of two assets. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.